2009
DOI: 10.1016/j.ygyno.2008.09.026
|View full text |Cite
|
Sign up to set email alerts
|

CYP1B1 expression in ovarian cancer in the laying hen Gallusdomesticus

Abstract: Objectives-Ovarian carcinoma is the most lethal gynecological malignancy. The genetic and molecular mechanisms that cause it still remain largely unknown. CYP1B1 is a cytochrome P450 enzyme that catalyzes the conversion of estrogens to genotoxic catechol estrogens which may cause DNA mutations and initiate ovarian epithelial cancer. Our objectives were to evaluate CYP1B1 expression, distribution and localization in the hen ovary and to determine if there is an increased CYP1B1 expression associated with, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…[17, 26, 30, 31, 33], but it is important to determine the precise pathways targeted by the biologically active components of flaxseed that affect the expression of a wide range of cancer targets.…”
Section: Introductionmentioning
confidence: 99%
“…[17, 26, 30, 31, 33], but it is important to determine the precise pathways targeted by the biologically active components of flaxseed that affect the expression of a wide range of cancer targets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the prevalence of delirium at the time of admission to an acute palliative care unit ranged from 28% to 42% [12,13]. The wide variation in the prevalence of delirium may be attributed to failure of recognition by the medical team and underuse of validated tools to screen for at-risk patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The wide variation in the prevalence of delirium may be attributed to failure of recognition by the medical team and underuse of validated tools to screen for at-risk patients [14,15]. Despite the implications of the presence of delirium on prognosis, few published studies are available on the frequency, course, and outcomes of standardized management of delirium in advanced cancer patients [2,13,16]. In this study, we examined the frequency, characteristics, and outcomes of delirium in patients with advanced cancer who were admitted to an APCU.This knowledge would assist clinicians in improving care for patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable example of the use of an animal model as a research tool is the utilization of the domestic hen (Gallus gallus domesticus) to study the molecular mechanisms involved in the development of ovarian carcinoma in humans [1][2][3][4][5][6]. Similar to what occurs in ovarian carcinoma, leiomyoma-like masses also occur on the oviduct of commercial strains of chickens [7,8].…”
Section: Introductionmentioning
confidence: 99%